Efficacy, safety and patient‐reported outcomes of ledipasvir/sofosbuvir in NS3/4A protease inhibitor‐experienced individuals with hepatitis C virus genotype 1 and HIV coinfection with and without cirrhosis (ANRS HC31 SOFTRIH study). Issue 3 (7th December 2017) - Rosenthal, E; Fougerou‐Leurent, C; Renault, A; Carrieri, MP; Marcellin, F; Garraffo, R; Teicher, E; Aumaitre, H; Lacombe, K; Bailly, F; Billaud, E; Chevaliez, S; et al.
Abstract : Objectives: Studies evaluating the efficacy and safety of the fixed‐dose combination ledipasvir (LDV)/sofosbuvir (SOF) in patients coinfected with HIV‐1 and hepatitis C virus (HCV) have mainly included treatment‐naïve patients without cirrhosis. We aimed to evaluate the efficacy and safety of this combination in treatment‐experienced patients with and without cirrhosis. Methods: We conducted a multicentre, open‐label, double‐arm, nonrandomized study in patients coinfected with HIV‐1 and HCV genotype 1 with and without cirrhosis, who had good viral suppression on their antiretroviral regimens. All patients were pretreated with a first‐generation NS3/4A protease inhibitor (PI) plus pegylated interferon/ribavirin. Patients received a fixed‐dose combination of LDV/SOF for 12 weeks, or for 24 weeks if cirrhosis was present. The primary endpoint was a sustained virological response (SVR) 12 weeks after the end of therapy. Secondary endpoints included safety, pharmacokinetics and patient‐reported outcomes. Results: Of the 68 patients enrolled, 39.7% had cirrhosis. Sixty‐five patients [95.6%; 95% confidence interval (CI): 87.6–99.1%; P < 0.0001] achieved an SVR, with similar rates of SVR in those with and without cirrhosis. Tolerance was satisfactory, with mainly grade 1 or 2 adverse events. Among patient‐reported outcomes, only fatigue significantly decreased at the end of treatment compared with baseline [odds ratio (OR): 0.36; 95% CI: 0.14–0.96; P = 0.04]. Mean tenofovir area under the plasma concentration–time curve (AUC) at week 4 was high, with mean ± SD AUC variation between baseline and week 4 higher in cirrhotic than in noncirrhotic patients (3261.57 ± 1920.47 ng/mL vs. 1576.15 ± 911.97 ng/mL, respectively; P = 0.03). Mild proteinuria (54.4%), hypophosphataemia (50.0%), blood bicarbonate decrease (29.4%) and hypokalaemia (13.2%) were reported. The serum creatinine level was not modified. Conclusions: LDV/SOF provided a high SVR rate in PI‐experienced subjects coinfected with HCV genotype 1 and HIV‐1, including patients with cirrhosis.